Evaluation of germination indices of Red Beanseed produced under water stress conditions and foliar application of zinc and manganese - مهدی براانی دستجردی; محمد رفیعی الحسینی; عبدالرزاق دانش شهرکی; سید مجتبی هاشمی جزی (علوم و فناوری بذر ایران)
This experiment was conducted as split factorial in a Randomized Complete Block Design (RCBD) with three replications in the research farm of Shahrekord University during 2010-2011 growing season. In this experiment irrigation treatments in three levels of: non water stress (irrigation after 50 mm evaporation from class A pan), moderate and sever water stress (irrigation after 70 and 90 mm evaporation from class A pan, respectively) were used as main factor, while factorial combination of Zn (spraying with pure water, spraying of 100 and 200 g Zn per hectare) and Mn (spraying with pure water, spraying of 150 and 300 g Mn per hectare) were used as sub-factor. The results showed that drought stress did not have any significant effect on germination rate, mean germination time, seedling length and dry weight while significant increases were obtained on germination percentage, coefficient of velocity of germination and seed vigor indices (I and II). Moreover, Mn foliar application in amount of 150 g per hectare had the highest germination percentage, germination rate, coefficient of velocity of germination,vigor indices (I and II) and the lowest mean germination time. The highest germination rate, seedling length and dry weight and vigor indices (I and II) was obtained for 100 g Zn per hectare